About pedagogical knowledge as artisan knowledge - Álvarez Gallego, Alejandro
In some way, the history of teaching is the history of the struggle for the autonomy of teachers, from the first clerics who became independent from the Church, to the most contemporary pedagogical movements. However, it is clear that these struggles have always been collective, not individual. A revaluation of the manual work and the contribution that gives the society the capacity of creation in the productive processes, is propitious to claim the know how to teach. Knowing how to teach is also a know-how. This article addresses the qualities of the process, based on the notion that knowledge has ethical and political character, implies a know-how, reaches all human beings and is eminently practical. Keywords: know-how, teaching, craft work.